Perlindungan Hukum Anak Sebagai Korban Tindak Pidana Pelecehan Seksual di Media Sosial - Ully Tri Ellen Mahulae; Ari Wibowo (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
Sexual harassment of children on social media is a crime that occurs from the flow of technological developments. The formulation of the problem is what are the weaknesses in the legal protection provisions for children who are victims of criminal acts of social harassment on social media before the enactment of Law Number 12 of 2022 concerning Crimes of Sexual Violence and whether Law Number 12 of 2022 concerning Crimes Sexual Violence Crime has provided ideal legal protection for children who are victims of criminal acts of sexual harassment on social media. The research uses a research typology in the form of normative law relating to norms, principles, statutory regulations, and related legal issues. The research approach taken is in the form of a statutory approach and a case approach. The results of the research are that the Criminal Code (KUHP), Law Number 31 of 2014 concerning Protection of Witnesses and Victims, and Law Number 35 of 2014 concerning Child Protection, the weaknesses of these three regulations are still general in nature, and has not explained specifically about sexual harassment on social media. Law Number 12 of 2022 concerning Crimes of Sexual Violence provides regulations and legal protection for children that are quite good and are in accordance with the forms of harassment that often occur on social media.